EXPLORING EFL VOCATIONAL STUDENTS IN WRITING DESCRIPTIVE TEXT THROUGH JOINT CONSTRUCTION OF GENRE BASED APPROACH: A CASE STUDY - Azzahra, Reva; Kusrin; Srisudarso, Mansyur (IKIP Siliwangi, 2024)
In writing class for EFL students, there are numerous factors to consider. These factors include students' learning styles, the role of the teacher, and the teaching methods used. There have been various researches that advocate genre-based approach and perceived it as effective to help EFL students improve their writing skills. However, the role of Joint Construction in this context is not specifically documented. While there are many possible reasons for this, one of them is that the role of collaboration and interaction in text production remains unexplored. As a concern to that, this research aimed to explore how joint construction of Genre based approace assists student in writing descriptive text. This research used case study research in the ten-grade of a vocational high school. To collect the data, the researcher conducted observations, reflective journals, and interviews which were analysed by thematic analysis. The finding revealed Joint construction engages students in enthusiastic learning experiences that help to overcome social isolation. The interaction that occured also has an impact on their ability to understand the text content. Collaborative learning emerged as a factor made students pleased with the learning process. Most of the students voiced that by holding discussion, they had the opportunity to explore ideas and knowledge. The positive responses shown by the students implied the joint construction positively contributes to building a more effective and diverse writing learning process for EFL vocational students.